An Analysis of Code Switching and Code Mixing in Fashion Program “I Look” on Net Tv - Renita Wati (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2020)
This study focuses on the form and function of code-switching and code-mixing used in the Fashion Program